Mitigation of eddy current heating during magnetic nanoparticle hyperthermia therapy. (2nd October 2016) - Stigliano, Robert V.; Shubitidze, Fridon; Petryk, James D.; Shoshiashvili, Levan; Petryk, Alicia A.; Hoopes, P. Jack
Abstract: Background: Magnetic nanoparticle hyperthermia therapy is a promising technology for cancer treatment, involving delivering magnetic nanoparticles (MNPs) into tumours then activating them using an alternating magnetic field (AMF). The system produces not only a magnetic field, but also an electric field which penetrates normal tissue and induces eddy currents, resulting in unwanted heating of normal tissues. Magnitude of the eddy current depends, in part, on the AMF source and the size of the tissue exposed to the field. The majority of in vivo MNP hyperthermia therapy studies have been performed in small animals, which, due to the spatial distribution of the AMF relative to the size of the animals, do not reveal the potential toxicity of eddy current heating in larger tissues. This has posed a non-trivial challenge for researchers attempting to scale up to clinically relevant volumes of tissue. There is a relative dearth of studies focused on decreasing the maximum temperature resulting from eddy current heating to increase therapeutic ratio. Methods: This paper presents two simple, clinically applicable techniques for decreasing maximum temperature induced by eddy currents. Computational and experimental results are presented to understand the underlying physics of eddy currents induced in conducting, biological tissues and leverage these insights to mitigate eddy current heating during MNP hyperthermia therapy. Results: Phantom studies show that the displacement and motion techniques reduce maximum temperature due to eddy currents by 74% and 19% in simulation, and by 77% and 33% experimentally. Conclusion: Further study is required to optimise these methods for particular scenarios; however, these results suggest larger volumes of tissue could be treated, and/or higher field strengths and frequencies could be used to attain increased MNP heating when these eddy current mitigation techniques are employed.